The Design And Fabrication Of Mini PET Bottle Shredder - SAHARUDIN, ABDULLAH KHABIR (Progress in Engineering Application and Technology, 2023)
This thesis presents a project on the design and fabrication of a mini PET bottle shredder machine model to save the cost of purchasing external materials by producing plastic chips for use in a Workshop Practice Course at a university in Malaysia. The project aims to replace aluminium and mild steel as work pieces with solid round plastic bars and result in innovations for learning sessions and workshop practice course lessons. The project includes studying the design and fabrication of the plastic shredder and shredding PET bottle plastic into tiny pieces, with a focus on safety factors, power requirements and efficiency. The literature review includes an introduction to plastics and their properties, and the methodology includes problem identification, a Gantt chart, and selection of appropriate manufacturing techniques. The results and discussion chapter includes analysis of the power required to drive the machine, and the structure and materials used, including angle bars for their strength and versatility. The chapter also includes a discussion of the shredder blade and spacer which were cut into 15 and 16 pieces respectively, as well as FEA Analysis on Alloy Steel Shredder Blade to get the maximum and minimum stress, strain, and displacement of three types of material of a shredder blade. However, the project did not fully achieve its stated objectives and some problems were encountered during implementation such as safety issues, cost concerns and problem with the distance between the shredder and spacer.